Forecasting electricity demand of Bangladesh and its relation with physical and natural variables using group method of data handling model - Miraz, Kazi Farhan Al; Biswas, Kallol; Rudra, MD. Rakin Yousuf (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.